2012
DOI: 10.2478/s11756-012-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype analysis and new chromosome number reports in Achillea species

Abstract: Cytological analyses were performed in nineteen accessions belonging to seven Achillea species. The results indicate that two species, A. filipendulina and A. tenuifolia, are diploid (2n = 2x = 18) and three species, A. bieberstinii, A. pachycephala, and A. aucheri are tetraploid (2n = 4x = 36). For two latter species, the chromosome numbers are new. Two ploidy levels of 2n = 6x = 54 and 2n = 8x = 72 in A. millefolium and two ploidy levels of 2n = 2x = 18 and 2n = 4x = 36 in A. santolina species were found. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
2
9
1
Order By: Relevance
“…Am1 and Am2 accessions were diploids (2n= 2x= 18) whereas the two other accessions (Am3 and Am4) showed tetraploid (2n= 4x= 36) level ( Figure 1 ). According to previous studies, Farsi et al (2009) and Khaniki (1995) , reported 2 n = 4 x = 36 chromosomes, while Sheidai et al (2009) and Ebrahim et al (2012) reported hexaploid and octoploid cytotypes. In our findings, we have observed a new ploidy level (2n= 2x= 18) for two Iranian accessions of Achillea millefolium (Am3, Am4) that were collected in northern parts of Iran.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Am1 and Am2 accessions were diploids (2n= 2x= 18) whereas the two other accessions (Am3 and Am4) showed tetraploid (2n= 4x= 36) level ( Figure 1 ). According to previous studies, Farsi et al (2009) and Khaniki (1995) , reported 2 n = 4 x = 36 chromosomes, while Sheidai et al (2009) and Ebrahim et al (2012) reported hexaploid and octoploid cytotypes. In our findings, we have observed a new ploidy level (2n= 2x= 18) for two Iranian accessions of Achillea millefolium (Am3, Am4) that were collected in northern parts of Iran.…”
Section: Resultsmentioning
confidence: 93%
“…Cluster analysis was done based on karyotypic characteristics (TCL, MCL, MAR and DRL) and karyotype asymmetry (TF% and S%) ( Figure 2 ) and agrees with Ebrahim et al (2012) . The results of cluster analyses divided the four accessions in two groups ( Figure 2 ); based on ploidy levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations